Discernment in the Letter to the Galatians - D. F. Tolmie (Acta Theologica, 2013)
Although discernment is not the primary focus of the Letter to the Galatians, a few references to this issue are found in the letter. These references are the focus of this study. After a brief overview of some approaches to discernment, three core elements of discernment are identified, namely reflection, choice and one’s relationship to God. Taking these elements as a point of departure, references to discernment in the following passages in the letter are investigated: 2:1-10; 2:11-21; 3:1-5 and 5:12-6:10.